Astronomia nos livros didáticos do ensino fundamental - (:unkn) unknown (Universidade Federal do Pampa, 2017)
Astronomy has an important thematic in the National Curricular Parameters of Elementary School constituting the Thematic Axis "Earth and Universe", we seek through this work to verify the unfolding of this indication of content in the textbooks of the National Program of TextBook used by science teachers of the municipal network of Education of the Municipality of Uruguaiana. With this purpose, the Nature Sciences Study Plan of the Uruguaiana Municipal Secretary of Education was analyzed, confirming the organization of the Science curriculum in order to meet the Curricular Parameters. It was verified with the teachers the execution of this Plan considering the contents of astronomy taught throughout the Final Years of Elementary School, showing a good agreement between planning and action. An analysis of astronomical concepts as well as the conceptual errors in astronomy present in these books was carried out comparing with other previous studies of the literature demonstrating an advance in the coverage of astronomy concepts in textbooks, but also the presence of classic conceptual errors. The improvement of the teaching of Astronomy in Sciences in the final years of Elementary Education, especially in the municipality of Uruguaiana, has planning and action that can be more aligned and effective with the continuing education of the teachers in the thematic of Astronomy aiming at comprehensiveness and depth in the approach of precognized contents in the national and municipal curricular proposals, as well as in the textbooks that show progress in the treatment of this theme.
Astronomy in elementary school textbooks
Keywords: Aquicultura; Aquiculture; Astronomia; Livros Didáticos; Erro conceitual; Astronomy; Textbooks; Conceptual Error; CNPQ::CIENCIAS EXATAS E DA TERRA